Real-Time PCR Assays for Detection and Quantification of Sweetpotato Viruses - Kokkinos, C D (Plant disease, 2006)
Viral diseases, especially those caused by mixed infections, are among the economically most important diseases of sweetpotato. The difficulties inherent in detecting, quantifying, and isolating viruses directly from sweetpotato have impeded progress in sweetpotato virus research. Real-time polymerase chain reaction (PCR) assays were developed for the detection and relative quantification in singleplex reactions of the potyviruses Sweet potato feathery mottle virus (SPFMV), Sweet potato virus G (SPVG), and Ipomoea vein mosaic virus (IVMV); the crinivirus Sweet potato chlorotic stunt virus (SPCSV); and the begomovirus Sweet potato leaf curl virus(SPLCV) directly from infected sweetpotato plants. There was no significant effect from potential inhibitors in total nucleic acid extracts from sweetpotato leaves on the performance of the real-time PCR assays. Virus titers of SPFMV, IVMV, and SPVG were quantified using real-time PCR and found to be lower in singly infected sweetpotato plants compared with singly infected Brazilian morning-glory (Ipomoea setosa Ker.) and I. nil cv. Scarlet O'Hara plants. Real-time PCR was a more efficient detection method for SPLCV than conventional PCR assay